Pengaruh Content Marketing dan Brand Trust Terhadap Keputusan Pembelian Produk Otomotif Studi Kasus Sumber Jaya Automotive Center Tahun 2025 - Egi Sapitri Ramadhani; Kemala Puji; Ade Candra (Universitas Muhammadiyah Pontianak, 2026)
This study aims to analyze the effect of content marketing and brand trust on purchasing decisions of automotive products at Sumber Jaya Automotive Center through Instagram. The research used a quantitative approach with questionnaires distributed to 155 respondents. Data analysis employed multiple linear regression, t-test, and F-test. The results show that content marketing and brand trust partially and simultaneously have a positive and significant effect on purchasing decisions. The coefficient of determination is 62%, indicating that both variables explain purchasing decisions, while the remaining is influenced by other factors.